Filipino working adolescents' conceptions of work - Yabut, Homer J. (Animo Repository, 2009)
Who is the Filipino working adolescent and where is he or she n coming from? The prese t study seeks to determine these adolescents, conceptions of the meanings of, reasons for, and contributions to their work. Data is gathered from focus group discussion held with 11 rural- and 12 urban based adolescents. Findings across rural and urban groups show that Filipino working adolescents give meaning to work as sustenance. They work because of financial difficulty. One positive benefit of work 1s being able to ·support one's family, while the negative contributions of work include compromised studies, compromised self-fulfillment, and compromised health. Rural adolescents approach work as a means to maintaining their survival and lifestyles, whereas urban adolescents approach work as a means to growth. Implications toward positive youth development are discussed and outlined.